Patients as Partners in the API Era - Kubick, Wayne (Applied clinical trials, 2018)
With respect to clinical studies, patients are anonymous "subjects," and we're enslaved to the case report file (CRF), designing studies to collect a set of data entered into EDC systems and moved along a complex, often recursive chain through data management, analysis, and interpretation. VAs Don Rucker, National Coordinator for Health IT, noted in a Health Information Technology (ONC) blog, "Open and accessible APIs (application programming interfaces) have transformed many industries. Within the healthcare industry, the Argonaut Project paved a path for engaging multiple stakeholders (providers, IT vendors, and consultants) to work together on a common implementation guide for using patient-focused APIs.